Revistas - Abierto, Espacio (Espacio Abierto, 2020)
TABULA RASAUniversidad Colegio Mayor de Cundinamarca. Bogotá, Colombia.Director: Eduardo Restrepo Nº 36. (octubre-diciembre 2020) REVUE D’ HISTOIRE DES SCIENCES HUMAINES.Centre Alexandre Koiré. París, Francia.Direction: Régine Plas et Nathalie Richard.Printemps 2020, n° 36Revista NERAUniversidade Estadual Paulista. Núcleo de Estudos, Pesquisas e Projetos de Reforma Agrária. Sâo Paulo, BrasilEditores: Camila Ferracini Origuéla, EstevanLeopoldo de Freitas Coca y Lorena Izá PereiraNº. 53. Mayo –agosto 2020GLOBAL DIALOGUE. International Sociological Association.Editors: Brigitte Aulenbacher, Klaus Dörre.Volume 10, Issue 3. December 2020POLIS.Universidad Autónoma Metropolitana. MéxicoEditor responsable: Mario Federico Bassols Ricardez.Vol. 16, núm. 1, enero-junio de 2020